# 5(3x-4)-1.10x=7-1.31(x+3)

## Simple and best practice solution for 5(3x-4)-1.10x=7-1.31(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 5(3x-4)-1.10x=7-1.31(x+3) equation:

5(3x-4)-1.10x=7-1.31(x+3)
We move all terms to the left:
5(3x-4)-1.10x-(7-1.31(x+3))=0
We add all the numbers together, and all the variables
-1.1x+5(3x-4)-(7-1.31(x+3))=0
We multiply parentheses
-1.1x+15x-(7-1.31(x+3))-20=0

We calculate terms in parentheses: -(7-1.31(x+3)), so:
7-1.31(x+3)
determiningTheFunctionDomain
-1.31(x+3)+7
We multiply parentheses
-1.31x-3.93+7
We add all the numbers together, and all the variables
-1.31x+3.07
Back to the equation:
-(-1.31x+3.07)

We add all the numbers together, and all the variables
13.9x-(-1.31x+3.07)-20=0
We get rid of parentheses
13.9x+1.31x-3.07-20=0
We add all the numbers together, and all the variables
15.21x-23.07=0
We move all terms containing x to the left, all other terms to the right
15.21x=23.07
x=23.07/15.21
x=1+4.2258064516129/8.1774193548387

`